Molecular Imaging: A Useful Tool for the Development of Natural Killer Cell-Based Immunotherapies - Gangadaran, Prakash; Ahn, Byeong-Cheol (Frontiers in Immunology, 2017)
Molecular imaging is a relatively new discipline that allows visualization, characterization, and measurement of the biological processes in living subjects, including humans, at a cellular and molecular level. The interaction between cancer cells and natural killer (NK) cells is complex and incompletely understood. Despite our limited knowledge, progress in the search for immune cell therapies against cancer could be significantly improved by dynamic and non-invasive visualization and tracking of immune cells and by visualization of the response of cancer cells to therapies in pre-clinical and clinical studies. Molecular imaging is an essential tool for these studies, and a multimodal molecular imaging approach can be applied to monitor immune cells in vivo, for instance, to visualize therapeutic effects. In this review, we discuss the usefulness of NK cells in cancer therapies and the pre-clinical and clinical usefulness of molecular imaging in NK cell-based therapies. Furthermore, we discuss different molecular imaging modalities for use with NK cell-based therapies, and their preclinical and clinical applications in animal and human subjects. Molecular imaging has contributed to the development of NK cell-based therapies against cancers in animal models and to the refinement of current cell-based cancer immunotherapies. Developing sensitive and reproducible non-invasive molecular imaging technologies for in vivo NK cell monitoring and for real-time assessment of therapeutic effects will accelerate the development of NK cell therapies.